Edward Said: the political intellectual & public spheres - Abu Elmeaza, Mohammed Salim (2015)
It has been a while now since his untimely passing on the 25th September,2003. Edward Said was one of the most prolific public intellectuals of the 20th century and his model of the intellectual is still a source of inspiration and respect. The present thesis engages in the debate around the intellectual and his/her relationship to the public sphere. It argues that Said’s thoughts in ‘Traveling Theory’ provide not only a theory of critical consciousness but also a politically empowering tool by use of which intellectuals are able penetrate spheres. Political public spheres have always been the defining spheres of intellectual figures throughout history. This triggers the starting point of connection; it suggests that Said’s model of the public intellectual represents a residual figure of the man of letters. It argues that both the man of letters and public intellectuals, in different epochs, were made to suffer the consequences of the transformations of the public spheres. Yet, Said’s model strikes a balance between the professional and the amateur. The political tool in the traveling theory acts here as a defining element of the intellectuals’ practice in achieving some form of balance between those spheres. Said’s theatre of thought has shown an indefatigable commitment to a connection between spheres; academic, public and political. It is through his politics of humanism that he beautifully conflates ideas and ideals. His politics in the struggle for Palestine is in fact a politics of truth, coexistence and reconciliation. This also manifested itself in his political writings, beginning from Question of Palestine and continuing until Freud and the non-European. Finally, it is his intellectual legacy and his legacy as a public intellectual that makes him so relevant to the recent Arab Spring. Having looked back at two years of his life (1967-1993) and recalled his spirit when looking at Arab intellectuals’ interventions in the Arab Spring, one can clearly glimpse Said’s underlying alternatives, which reverberated in some of the Arab intellectuals as a model of the intellectual who can act beyond ideology.